Rancang Bangun Aplikasi Stok data Barang Berbasis Web Menggunakan Metode Prototype ( Studi Kasus Rani Cell) - Bagas mustakim; Donna Setiawati; Fariyono Fariyono (JITU : Journal Informatic Technology And Communication, 2022)
The rani cell counter is one of the internet data voucher counters, credit and cellphone accessories. Constraints experienced by the cell counter, namely in recording and managing stock of goods data are still done manually, data recording of incoming and outgoing goods is still recorded in the archive book so that it is less effective and makes it difficult in the process of searching for goods data. In addition, the owner cannot find out various reports or monitor the number of stock data items. Rani Cell Counter requires a web-based stock management facility that can facilitate Rani Cell Counter in recording and managing stock items. The research method used is the prototype method. The results of this study are a stock data application system that can help admins and owners of Rani Cell counters in recording incoming and outgoing goods, printing reports of incoming and outgoing goods and monitoring stock data of goods at branch and central counters